MRM810 : Digital records forensic and e-discovery / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2020)
The course is designed for information professional background in understanding the electronic evidence field. Digital Forensic is one aspect of authentication process of information to be used in legal proceeding, apart from the Electronic Discovery which offers skill of drilling into detail of information and records. The skill and knowledge acquired from both domains serve as an important aspect in expending the field of information domain. The course discusses the trends, enforcement functions and also highlights the importance of understanding the various computer devices, forensic processes and techniques as well as forensic tools to counter the threats. Student also will be taught practical aspect of conducting the forensic investigation as well performing electronic discovery